Public Authority in Interim Replacement of Members of the House of Representatives - Rahmat Adi Setiawan (Faculty of Law Universitas Muhammadiyah Purwokerto, 2020)
The House of Representatives is a people's representative institution or legislative body. Membership of the House of Representatives, both at the central and regional levels, can be replaced with other members through a mechanism, namely Interim Replacement. The purpose of interim replacement is to maximize the performance of legislators effectively and efficiently. However, there is a problem, namely the replacement of members of the legislature in the middle of their term of office. This study aims to analyze the mechanism of interim replacement of members of the House of Representatives and how the involvement of voters in the intertime replacement mechanism. This research is normative juridical research using secondary data as the primary data in the form of legislation, research results, and journals. Based on the research results, the interim replacement mechanism does not involve the public, namely voters. Disputes between members of the legislature and the supporting party cannot be avoided due to the inappropriate process of implementing the mechanism. It is necessary to improve the mechanism for the Interim Replacement of members of the House of Representatives, which is not only the authority of political parties but also the public authority, namely the constituent voters.Keywords: Public Authority, Interim Replacement, Representative